The First Synthesis of Spirocyclic Sulfates from Tertiary Cyclopropanols and Their Reaction with Normant Homocuprates - Shklyaruck, Denis G.; Fedarkevich, Artsiom N.; Kozyrkov, Yurii Yu. (Synlett, 2014)
Spirocyclic sulfates of 2- and 3-(hydroxyalkyl)cyclopropanols, obtainable through the Kulinkovich reaction from β-and γ-hydroxy carboxylic acid esters, respectively, were synthesized for the first time. The possibility of regio- and stereoselective alkylating the spirocyclic sulfates by using Normant homocuprates has been demonstrated.
Keywords: cyclopropanols; spiro compounds; sulfates; cuprates; alkylation